2019
DOI: 10.3390/buildings9020039
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Seismic Response on the Infill Masonry Walls of a 15-Storey Reinforced Concrete Structure in Nepal

Abstract: Following the strong earthquake on April 25, 2015 in Nepal, a team from the University of Porto, in collaboration with other international institutions, made a field study on some of the most affected areas in the capital region of Kathmandu. One of the tasks was the study of a high-rise settle of buildings that were damaged following the earthquake sequence. A survey damage assessment was performed to a 15-storey infilled reinforced concrete structure, which will be detailed in the manuscript. Moreover, ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…However, the infilled RC frame buildings have often demonstrated a different seismic performance due to the presence of the masonry, both in terms of seismic demand and capacity (Smith, 1962;Crisafulli, 1997;Rodrigues et al, 2018;Furtado et al, 2019). Sometimes after an earthquake, soft story mechanisms, short columns effects, or additional torsional actions due to an irregular distribution of infills can be observed (Dolsek and Fajfar, 2001;Ricci et al, 2011Ricci et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…However, the infilled RC frame buildings have often demonstrated a different seismic performance due to the presence of the masonry, both in terms of seismic demand and capacity (Smith, 1962;Crisafulli, 1997;Rodrigues et al, 2018;Furtado et al, 2019). Sometimes after an earthquake, soft story mechanisms, short columns effects, or additional torsional actions due to an irregular distribution of infills can be observed (Dolsek and Fajfar, 2001;Ricci et al, 2011Ricci et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [5], Furtado et al observed the impact of proving infill walls in a 15 story RC building and conclude in 20% increment in its story shear and base shear results. However, in most cases, the influence of infill walls may cause an extensive damage or collapse of structure [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the previous studies have been summarized that unreinforced brick masonry infill contributes to increase the lateral strength and stiffness but decrease the ductility of infilled RC frame structures [2][3][4][5]. However, the brick masonry infill recurrently failed out of the plane direction in many cases of earthquake events [6]. For providing excellent ductility performance on infilled frame structure and preventing the out of the plane failure of masonry infills, several strengthening methods have been developed by researchers such as the use mesh carbon and mesh glass [7], the use passive compression method [8], and reinforcements embedded in mortar bed joints.…”
Section: Introductionmentioning
confidence: 99%